Formation of anomalous gas fields of helium and hydrogen in the Cat Ba, Co To and Bach Long Vi islands, northern Vietnam - Nadezhda, Syrbu; Le Duc, Luong; Andre, Kholmogorov; Nguyen, Hoang (Vietnam Journal of Earth Sciences, 2021)
Data of methane, helium and hydrogen concentrations in the mineral waters, as well as in the subsurface atmosphere, of the Cat Ba, Co To and Bach Long Vi islands, shows that the regions belong to degassing zones of hydrogen and helium, and points at gas condensate potential of the Bac Bo sedimentary basin. A joint transit of these gases via the fault structures was established. Distribution patterns of hydrogen and helium concentrations from these islands (Tonkin Gulf) were obtained from the gas and water sample data. Thermogenic and metamorphogenic gases detected in hydrogeological wells on Cat Ba island and gas anomalies in subsurface gas indicate natural gas emission through permeability zones. The work was carried out within the framework of the joint Russian-Vietnamese Laboratory on Marine Geosciences (V.I.Il`ichev Pacific Oceanological Institute FEB RAS and Institute of Marine Geology and Geophysics, VAST). The research involves the staff and scientific equipment of the new innovative Laboratory for Integrated Research of the Environment and Mineral Resources (LIREMR) of the POI FEB RAS, created within the framework of the SCIENCE national project.